2007
DOI: 10.1139/y07-068
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial expression of endoglin in normocholesterolemic and hypercholesterolemic C57BL/6J mice before and after atorvastatin treatment

Abstract: Endoglin (CD105) is a homodimeric transmembrane glycoprotein strongly related to transforming growth factor (TGF)-beta signaling and many pathological states. In this study, we wanted to evaluate whether endoglin is expressed in normocholesterolemic and hypercholesterolemic C57BL/6J mice as well as whether it is affected by atorvastatin treatment in these mice. C57BL/6J mice were fed with chow diet or an atherogenic diet for 12 weeks after weaning. In 2 atorvastatin-treated groups, mice were fed the same diets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 43 publications
2
10
2
Order By: Relevance
“…We found only a weak expression of endoglin inside atherosclerotic plaque and almost no expression by smooth muscle cells in vessel media. These results are consistent with our previous studies of non-atherosclerotic vessels in normoand hypercholesterolemic mice 7,22) suggesting that endoglin is expressed predominantly by the vessel endothelium in mice. This discrepancy with previous studies in humans might reflect the differences between human and mice atherogenesis.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…We found only a weak expression of endoglin inside atherosclerotic plaque and almost no expression by smooth muscle cells in vessel media. These results are consistent with our previous studies of non-atherosclerotic vessels in normoand hypercholesterolemic mice 7,22) suggesting that endoglin is expressed predominantly by the vessel endothelium in mice. This discrepancy with previous studies in humans might reflect the differences between human and mice atherogenesis.…”
Section: Discussionsupporting
confidence: 94%
“…In contrast, in our previous study we found that atorvastatin decreased endoglin expression by both hypolipidemic and pleiotropic effects 6,7) ; however, there are some substantial differences when we compare with the results of this study. Firstly, the previous study used different mouse strains, apoE-deficient 6) and C57BL/6J mice 7) .…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…Our previous study focused on endothelial expression of endoglin in the aorta where no atherosclerosis was detected, demonstrating reduced endoglin expression after statin treatment 45) . Moreover, pitavastatin treatment suppressed Angiotensin -induced enhancement of cardiac TGF-1 expression and Smad2/3 signaling and prevented fibrotic changes 46) .…”
Section: Discussionmentioning
confidence: 99%
“…It must be stated that direct evidence of this working pathway is complicated due to some limitations of in vivo experiments. In general, it is complicated to precisely explain endoglin participation in the regulation of the proposed pathways and atherosclerosis in vivo because endoglin is exclusively expressed in endothelial cells in mice 4,45) , while other members of the cascade, including ALK, Smad proteins and VEGF, are also expressed in the whole vessel wall. Other authors also showed increased endoglin expression in smooth muscle cells, and in macrophages in human and porcine atherosclerotic lesions 8,18) .…”
Section: Discussionmentioning
confidence: 99%